(untitled) (Pedagogy of Higher and Secondary Education, 2022)
The author reveals how to use art teachers, through which the children disappear tension, anxiety, students learn to freely express their thoughts. Through the use of expressive psycho-social experiences students receive, new impressions, do not behave as they are required, as well as they want. Designing educational situations in the classroom Ukrainian literature sent to reinforce the positive feelings of "Г" student, to strengthen its own forces to self-development.